Unveiling giant hidden Rashba effects in two-dimensional Si2Bi2 - Seungjun Lee (Nature Portfolio, 2020)
Abstract Recently, it has been known that the hidden Rashba (R-2) effect in two-dimensional materials gives rise to a physical phenomenon called spin-layer locking (SLL). However, not only its underlying fundamental mechanism has been unclear, but also there are only a few materials exhibiting weak SLL. Here, through the first-principles density functional theory and model Hamiltonian calculation, we reveal that the R-2 SLL can be determined by the competition between the sublayer–sublayer interaction and the spin–orbit coupling, which is related to the Rashba strength. In addition, the orbital angular momentum distribution is another crucial point to realize the strong R-2 SLL. We propose that a 2D material Si2Bi2 possesses an ideal condition for the strong R-2 SLL, whose Rashba strength is evaluated to be 2.16 eVÅ, which is the greatest value ever observed in 2D R-2 materials to the best of our knowledge. Furthermore, we reveal that the interlayer interaction in a bilayer structure ensures R-2 states spatially farther apart, implying a potential application in spintronics.